1989
DOI: 10.1161/01.res.65.5.1409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a thromboxane A2 analogue and prostacyclin on lung fluid balance in newborn lambs.

Abstract: We have previously shown that the pulmonary venoconstriction produced by a stable thromboxane A 2 analogue (STAJ is attenuated by prostacyclin (PGIi), but PGI, increases the STA 2 -induced edema. The present study was designed to determine the effects of STA 2 and PGI 2 on the fluid balance in isolated blood-perfused newborn lamb lungs. Vascular permeability was evaluated by use of the fluid filtration coefficient (Kf) and the osmotic reflection coefficient for total proteins (cr, hematocrit-protein double ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…This is clearly different from the experience reported in the present study [as well as that reported by other investigators (12,21)] in which PGI 2 alone had no effect on K f . Even in the presence of U-46619, the increase in K f associated with PGI 2 exposure was much more modest than that suggested by Yoshimura et al (38). The reason for this difference is unclear, although fundamental differences in the experimental models are likely to be important [e.g., a sanguineous perfusate was utilized in the Yoshimura study (38), whereas an asanguineous buffer was used in the present study].…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…This is clearly different from the experience reported in the present study [as well as that reported by other investigators (12,21)] in which PGI 2 alone had no effect on K f . Even in the presence of U-46619, the increase in K f associated with PGI 2 exposure was much more modest than that suggested by Yoshimura et al (38). The reason for this difference is unclear, although fundamental differences in the experimental models are likely to be important [e.g., a sanguineous perfusate was utilized in the Yoshimura study (38), whereas an asanguineous buffer was used in the present study].…”
Section: Discussionmentioning
confidence: 52%
“…Even in the presence of U-46619, the increase in K f associated with PGI 2 exposure was much more modest than that suggested by Yoshimura et al (38). The reason for this difference is unclear, although fundamental differences in the experimental models are likely to be important [e.g., a sanguineous perfusate was utilized in the Yoshimura study (38), whereas an asanguineous buffer was used in the present study]. Furthermore, the total amount of PGI 2 administered in the Yoshimura study was more than 100 times greater than that of the present study (about 300 µg over 180 min in the Yoshimura study vs. 2.6 µg in the present study).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations